Proses Pembuatan Alat Musik Gesek Tehyan Di Sanggar Putra Ula Kota Tangerang - Kawistara, Muhammad Galih; Hadiyatno, Hadiyatno; Permana, Rian (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2024)
This research aims to find out and study the process of making tehyan as a Betawi traditional musical instrument at Tangerang. This study used a descriptive qualitative method. The research data was obtained through tehyan craftsmen. Data collection techniques were carried out by observing documentation and in-depth interviews, the collected data were described and analyzed about the process of making tehyan by the craftsmen. This research is limited to the media selection, tools and materials used in making, and the process and stages of making tehyan. The researcher’s interest in this research is due to the lack of public interest and appreciation of tehyan as a cultural heritage, which needs attention so tehyan sustainability is maintained, and hopes to motivate other researchers to continue this research that author has done. So tehyan sustainability is maintaned.Keywords: the making of, media, material, Tehyan